Localization of Tec29 to ring canals is mediated by Src64 and PtdIns(3,4,5)P(3)-dependent mechanisms. - Lu, N.; Guarnieri, D.J.; Simon, M.A. (The EMBO Journal, 2004)
Two tyrosine kinases, Src64 and Tec29, regulate the growth of actin rich-ring canals in the Drosophila ovary. We have shown previously that Src64 directs the localization of Tec29 to ring canals, but the mechanism underlying this process was unknown. Here, we show that Tec29 localizes to ring canals via its Src homology 3 (SH3) and Src homology 2 (SH2) domains. Tec29 activity is required for its own ring canal localization, suggesting that a phosphotyrosine ligand for the SH2 domain is generated by Tec29 itself. Src64 regulates this process by phosphorylating Y677 within the kinase domain of Tec29, an event required for Tec29 activation. We also show that the pleckstrin homology (PH) domain of Tec29 has dual functions in mediating Src64 regulation. In the absence of Src64, the PH domain prevents Tec29 ring canal localization. In the presence of Src64, it enhances membrane targeting of Tec29 by a PI(3,4,5)P(3)-mediated mechanism. In the absence of its PH domain, Tec29 constitutively localizes to ring canals, but still requires Src64 for full activation.